Tipologi Kausatif Formal Bahasa Jawa Kuna - Erawati, Ni Ketut Ratna (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2014)
The Old Javanese language (OJL) is a language with rich morphemes that form words. This implicates the syntactic process in the language. One example of a syntactic alternation is a causative. Causative is a valence-raising mechanism in the structure of a clause. This study aims to describe the formal causative in OJL. Causative in OJL is morphologically marked on the verb. Causative verbs can be formed from non-causative ones, such as adjectives and basic verbs. In OJL there are three types of causative: morphological, lexical, and analytic causative. Morphological causative is formed by affixes like mang-/ng+-i, paha-+-in-, -um-+-akên (a), infix -um-, and -in-/-an, -in- (in the passive voice). Lexical causative is the basic form which has a causative meaning. Analytic causative is formed by adding a verb form *gawe*, *matangyan*, and *hetu*. Intransitive verb clause is diathesis patientive. The transitive verb clause has two macro roles, namely actor and undergoer. When the two macro situations are merged into a single macro situation, the particles are connected by conjunctions: *sawet*, *matangyan*, *apan*, and *karana*.